2001
DOI: 10.1046/j.1365-3059.2001.00594.x
|View full text |Cite
|
Sign up to set email alerts
|

Gas chromatography–mass spectrometry analyses of volatile organic compounds from potato tubers inoculated with Phytophthora infestans or Fusarium coeruleum

Abstract: Volatile organic compounds (VOCs) collected from potato tubers inoculated with Phytophthora infestans (late blight), Fusarium coeruleum (dry rot) or sterilized distilled water (as a control) were analysed using gas chromatography±mass spectrometry (GC±MS) and gas chromatography±flame ionization detection (GC±FID). A total of 52 volatiles were identified by GC±MS in the headspaces above P. infestans-and F. coeruleum-inoculated tubers after incubation for 42 days in the dark at 108C. Of these VOCs, the six most … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
52
0
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(56 citation statements)
references
References 22 publications
0
52
0
1
Order By: Relevance
“…All three compounds have repeatedly been reported in the context of plant pathogenesis: nonanal and 2-ethyl hexanol were found in the headspace of potato (Solanum tuberosum) tubers infected with different fungi (de Lacy Costello et al, 2001) and of various biological control bacteria (Dilantha Fernando et al, 2005), nonanal was released from whiteflyinfected beans (Phaseolus vulgaris; Birkett et al, 2003), and both nonanal and 2-ethyl hexanol were reported to have in vitro antifungal (Dilantha Fernando et al, 2005) and bactericidal (Nakamura and Hatanaka, 2002) activities.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…All three compounds have repeatedly been reported in the context of plant pathogenesis: nonanal and 2-ethyl hexanol were found in the headspace of potato (Solanum tuberosum) tubers infected with different fungi (de Lacy Costello et al, 2001) and of various biological control bacteria (Dilantha Fernando et al, 2005), nonanal was released from whiteflyinfected beans (Phaseolus vulgaris; Birkett et al, 2003), and both nonanal and 2-ethyl hexanol were reported to have in vitro antifungal (Dilantha Fernando et al, 2005) and bactericidal (Nakamura and Hatanaka, 2002) activities.…”
Section: Discussionmentioning
confidence: 91%
“…However, although 2-ethyl hexanol has repeatedly been reported in the context of pathogenesis (de Lacy Costello et al, 2001;Nakamura and Hatanaka, 2002;Dilantha Fernando et al, 2005), the compound is also a very common contaminant. In fact, no convincing study has ever reported a clear case of plant-derived 2-ethyl hexanol (W. Boland, personal communication).…”
Section: Discussionmentioning
confidence: 99%
“…VOC induction has also been detected in fungal inoculated potatoes (De Lacy Costello et al, 2001;Kushalappa et al, 2002), peanuts (Cardoza et al, 2002), wheat (Piesik et al, 2007), onions (Vikram et al, 2005), and higher ethylene emission from Monterey pine (Bonello et al, 2001). Plant responses to biotic and abiotic perturbation often reduce the severity of future damage through complex changes.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, certain pathogens may be severe enough, or infect maize in such a manner, that VOC induction results (Piesik et al 2011, current study). Studies with other plant species have also detected VOC induction after pathogen infection (Bonello et al 2001, De Lacy Costello et al 2001, Cardoza et al 2002, Vikram et al 2005. More needs to be understood to determine whether certain mechanisms of pathogen infection result in VOC induction and other types of pathogens do not, and the extent to which this is generalizable across plants and pathogens.…”
Section: Discussionmentioning
confidence: 99%